Nanoparticles as molten salts thermophysical properties enhancer for concentrated solar power: A critical review - Aljaerani, Hatem Ahmad; M., Samykano; R., Saidur; A. K., Pandey; K., Kadirgama (Elsevier Ltd, 2021)
The emphasis on exploiting solar power has efficaciously engaged the concentrated solar power (CSP) technology towards producing electricity from solar thermal energy. CSP technology’s key element is molten salts, which function as thermal energy storage (TES) to absorb and store the sun’s thermal energy and as a heat transfer medium to transfer the stored thermal energy to a steam generator for electrical energy production. The thermophysical properties enhancement of molten salt through the integration of additives such as nanoparticles permits the molten salt to store additional solar thermal energy by improving its heat transfer properties. This, in due course, leads to an overall enhancement of the CSP plant efficiency and electricity cost. Various types of inorganic nanoparticles such as Alumina, Copper Oxide, and Titania have been studied with different types of molten salts to enhance their thermophysical properties, especially those related to CSP applications. As such, the present review aims to discuss the recent advances in nano-enhanced molten salt (NEMS) and the nanoparticles used to date to enhance molten salts behavior for CSP systems. In addition, important topics related to NEMS, such as the stability of nanoparticles and nanostructures’ formation, are also discussed. The article also focuses on the different types of nanoparticles used as thermophysical enhancers and their enhancement logics. Besides, the effect of nanoparticle assets such as mass percentage, size, and shape and how they may positively or negatively affect the thermophysical properties of molten salts are also presented in this review. The related publications in this field have shown an increasing focus on enhancing molten salts’ thermophysical properties every year. Most of these experiments were focused on improving the heat capacity of nitrate or carbonate salts. Additionally, the dendritic nanostructures were reported to have a long-range effect that may enhance the heat capacity. Also, the studies on nanoparticle concentration and morphology reveal that these factors significantly influence the molten salt’s thermophysical properties. This review is anticipated to provide an outline of the works done related to NEMS and to benefit the researchers in the field.